2021
DOI: 10.1037/sah0000267
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and consequences of internalized stigma assessed through the Internalized Stigma of Mental Illness Scale for people living with mental illness: A scoping review and meta-analysis from 2010.

Abstract: Internalized stigma (IS), in addition to the illness itself, is one of the major challenges that people with mental health problems have to face. The aim of this scoping review and meta-analysis is to update knowledge about this issue and to investigate the influence of different sociodemographic, psychosocial, and clinical variables on IS. English and Spanish articles were searched between 2010 and 2019, in different databases, with no restriction on culture or geographical area. Only studies that used the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
6
28
1
Order By: Relevance
“…Although there were small mean differences in stigma endorsement across the five conditions, generally, the relationship between MI stigma and important outcomes was not impacted. Consistent with prior research (e.g., Boyd et al, 2014;Del Rosal, et al, 2020), personal, perceived, and internalized stigma were all associated with increased depressive and anxiety symptoms, self-stigma of seeking psychological help, treatment intentions, and receiving treatment in the past year, and negatively associated with attitudes toward seeking psychological help and self-esteem. None of these relationships varied as a function of labeling condition.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although there were small mean differences in stigma endorsement across the five conditions, generally, the relationship between MI stigma and important outcomes was not impacted. Consistent with prior research (e.g., Boyd et al, 2014;Del Rosal, et al, 2020), personal, perceived, and internalized stigma were all associated with increased depressive and anxiety symptoms, self-stigma of seeking psychological help, treatment intentions, and receiving treatment in the past year, and negatively associated with attitudes toward seeking psychological help and self-esteem. None of these relationships varied as a function of labeling condition.…”
Section: Discussionsupporting
confidence: 85%
“…There is a substantial body of research demonstrating the relationship between stigma and both psychosocial and mental health-related variables. A meta-analysis of internalized stigma (Livingston & Boyd, 2010), a replication 10 years later (Del Rosal et al, 2020), and a multinational review of studies using the ISMI (Boyd et al, 2014) all found that internalized stigma was consistently associated with decreased self-esteem and more severe symptoms. But research on the relationship between stigma and help-seeking is more mixed, with studies finding both positive and negative relationships between stigma mechanisms and help-seeking (Clement et al, 2015).…”
Section: How Terminology Can Impact Stigma Endorsement and Its Relati...mentioning
confidence: 99%
“…Psychologists and other social scientists have achieved remarkable innovations over the past several decades in research methods for studying time 137 , 138 . Yet, according to meta-analyses, only a minority of studies focused on associations between stigma and health use longitudinal methods 34 , 73 , 139 , 140 . Moreover, decades of research have yielded a toolbox of evidence-based strategies to intervene and reduce stigma, such as through education, contact between people with and without stigmatized statuses, and policy change 141 145 .…”
Section: A Time-based Research Agendamentioning
confidence: 99%
“…Coming from rural background and being single were associated with high stigma scores in a study from Ethiopia in schizophrenia in a hospital-based study [2]. In a recently published review and meta-analysis of studies assessing stigma using ISMI in patients with severe mental illness, Rosal et al reported weak and inconsistent relationship of stigma with sociodemographic variables such as gender, age, occupation, education and marital status [32]. Similar weak associations with sociodemographic variables were reported in another systemic review of stigma in schizophrenia spectrum disorders [31].…”
Section: Plos Onementioning
confidence: 99%